Police Use of Live Ammunition in Student Protest Fatality: Penggunaan Peluru Tajam oleh Polisi dalam Insiden Kematian pada Demonstrasi Mahasiswa - Galih Aldi Wiyogo; Emy Rosnawati (Academia Open, 2025)
General Background: Violence by security forces during public demonstrations remains a critical human rights concern, particularly when it results in civilian deaths. Specific Background: In Indonesia, several incidents involving police shootings during protests—most notably historical cases such as the 1998 Semanggi tragedy—have raised questions about the proportional use of force and adherence to operational procedures. Knowledge Gap: Despite public attention, there is limited analytical discussion grounded in legal perspectives regarding the accountability of police officers who use lethal force during riot control situations. Aims: This study analyzes the death of a student shot by a police officer during a riot, focusing on procedural compliance, legal responsibility, and avenues for justice for victims’ families. Results: The analysis indicates that the use of live ammunition against unarmed demonstrators violates established protocols, which prioritize non-lethal crowd-control measures, and such actions should be subject to legal investigation regardless of intent. Novelty: The study integrates expert legal opinion with historical context to clarify the standards governing police conduct during demonstrations and the legal consequences of procedural violations. Implications: Strengthening regulatory frameworks, improving dissemination of operational guidelines to officers, and ensuring transparent investigations are essential to prevent recurrence, uphold the rule of law, and maintain public trust in law enforcement institutions. Highlights: Lethal weapons were deployed contrary to prescribed non-deadly crowd-management rules. Families of victims retain the right to pursue justice through formal legal channels. Transparent investigation and regulatory revision are necessary to prevent future incidents. Keywords: Police Use Of Force; Live Ammunition; Student Protest; Legal Accountability; Crowd Control